Women’s empowerment model in home-based industries in East Java Province, Indonesia - Emy Susanti; Siti Mas'udah (Faculty of Social and Political Science, Universitas Airlangga, 2017)
This study aimed to classify the role of women, gender and characteristics of home-based industries that were managed by women in two cities of East Java Province. This study also tried to identify strengths, weaknesses and challenges faced by these women, especially impoverished women. The research employed qualitative method supported by quantitative data. The data collected through structured interviews guided by questionnaires and indepth interviews. Three main results were attained. First, it was related to the characteristics of women workers, the role of multi-burdened women, the flexible working hours, formal education but unrelated to work, and low income but still importantly needed to support economic condition. Second, three networks were found: network between manager/owner and workers that was informal and family-oriented, network between managers and local government for marketing and training, and network with the private sector for access to capital and business development. Third, the model of empowering small home-based industries should consider the specific needs of women. In other words, there is a requisite for practical and strategic gender needs that has to be comprehended and become the basis for the planning and development to conduct activities and programs for women.